2011
DOI: 10.1177/2041297510394075
|View full text |Cite
|
Sign up to set email alerts
|

Application of continuous spindle speed variation for chatter avoidance in roughing milling

Abstract: This paper investigates the effectiveness of the continuous spindle speed variation (CSSV) technique as a chatter-suppression strategy in the milling process. For this purpose, a two-fold study was carried out: on the one hand, a simulation analysis, and on the other, experimental tests. First, the semidiscretization method has been extended to n-mode systems in any spatial direction and modified to include simulation capabilities concerning spindle speed variation with different waveforms. A new kind of stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…To suppress the regenerative chatter described above, sinusoidal spindle speed variation (SSV) is employed extensively in the tuming [23][24][25] and the milling [26][27][28]. In the research on external cylindrical grinding, Inasaki et al [29] first simulated the grinding process with a sinusoidal workpiece speed variation and concluded that this is an effective method to suppress the grinding chatter.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the regenerative chatter described above, sinusoidal spindle speed variation (SSV) is employed extensively in the tuming [23][24][25] and the milling [26][27][28]. In the research on external cylindrical grinding, Inasaki et al [29] first simulated the grinding process with a sinusoidal workpiece speed variation and concluded that this is an effective method to suppress the grinding chatter.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the SSSV did not influence the surface finish negatively even when it was applied during a stable turning operations. Bediaga et al, (2011) tested effectiveness of the continuous spindle speed variation (CSSV) technique as a chattersuppression strategy in the milling process. They proposed a stability map for different amplitude and frequency variations in order to optimize the parameter selection when machining.…”
Section: Other Methodsmentioning
confidence: 99%
“…This technique is based on the introduction of a perturbation in the spindle speed command. There are different methods for varying the spindle speed, including sinusoidal [35][36][37][38], triangular [39], rectangular [31], random [40], or continuous linear perturbation [41]. The sinusoidal signal has emerged as the most efficient technique compared to random, rectangular, or triangular shapes.…”
Section: Continuous Spindle Speed Variation (Cssv)mentioning
confidence: 99%